Antioxidant and anti-acetylcholinesterase potential from waste of selected solanaceous plants: isolation and identification of the active compound - Muhammad, Khan (2015)
Alzheimer‘s disease (AD) is one of the most common forms of dementia, affecting the elderly population globally. The occurrence of the ailment is on the rise; one person is being effected every 71 seconds. This rate is higher than many other fatal diseases, e.g., cancer, stroke, and heart failures. Therefore, searching for compounds with minimal side effects along with significant activity against acetylcholinesterase (AChE), are needed to be discovered to fight AD. In order to achieve this goal the study was undertaken to screen 32 medicinal plants based on their total phenolic contents (TPC), total flavonoid contents (TFC), antioxidant activity (AOA), and antiacetylcholinesterase activity (AChE) to select the best source of the active compounds that can be used for the treatment of Alzheimer‘s disease. For the purpose, crude extracts from all 32 plants were subjected to determine TPC, TFC, AOA, and anti- AChE activity, and 3 plants out of 32 were finally selected for further study. The selected lants include Solanum tuberosum (Potato), Solanum melongena (Brinjals), and Capsicum annuum (Chilli). All three species belong to genus solanum and family solanaceae. TPC was determined following the Folin-Ciocalteu colorimetric method and TFC was determined using aluminium chloride colorimetric assay. AOA was determined by DPPH-scavenging and β-carotene assay methods, while anti-AchE activity was assayed by Ellman‘s method. A pure compound α-solanine was isolated by TLC, followed by HPLC and prep-HPLC. The fractions and isolated compound both showed significant bioactivities. The crude extract of S. tuberosum showed the highest anti-AChE activity (IC50 = 689.9 μg/mL), followed by, S. melongena (IC50 = 731.99 μg/mL), and C. annuum (IC50 = 851 μg/mL). Purified α-solanine demonstrated the second highest anti-AchE activity (IC50 = 725.70 μg/mL). A similar trend was seen for their antioxidant activity. In this case, TPC and TFC showed significant correlation with AOA and anti-AchE activity; attributing the bioactivities to be due to phenolic and flavonoids compounds present in plant fractions. The correlation between AChE,DPPH, TPC and TFC, were all found to be statistically significant (P<0.05). Furthermore, the finding shows that a good antioxidant compound can be a potent inhibitor of AChE. The data revealed that S. tuberosum fraction had higher activity compared to α- solanine that might be due to the synergistic effect of alkaloidalcompounds and the polyphenols present in the crude extract. The structure of the isolated compound was elucidated by different chromatographic and spectroscopic techniques including HPLC, FTIR, NMR and LC-MS. The research results indicated that Solanum species could be the candidates of choice in further search for new AchE inhibitors